2022
DOI: 10.5005/ijcdas-53-3-153
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Oxidant Treatment in Obstructive Sleep Apnoea Syndrome

Abstract: Purpose. To investigate whether oral intake of N-acetylcysteine (NAC) is a treatment option in patients with obstructive sleep apnoea syndrome (OSAS).Methods. Twenty patients with OSAS were enrolled in the study. After polysomnography (PSG), they were randomly assigned to receive a placebo (n=10) and NAC (n=10). A repeat PSG was done after the treatment period of 30 days. Fasting venous samples were collected for various biochemical analysis. Results.In the patients of NAC group, compared to their baseline val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Moreover, this combinational antioxidant treatment reduced apnoea index and excessive day-time sleepiness, the most common symptom of OSAS which significantly impacts OSAS patients' quality of life [114]. Similarly, OSAS patients treated with NAC exhibited decreased lipid peroxidation and increased levels of glutathione [115]. NAC treatment significantly improved sleep and respiratory parameters indicated by reduced apnoea index, apnoea related-arousals, oxygen desaturations per hour and Epworth sleepiness score [115].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, this combinational antioxidant treatment reduced apnoea index and excessive day-time sleepiness, the most common symptom of OSAS which significantly impacts OSAS patients' quality of life [114]. Similarly, OSAS patients treated with NAC exhibited decreased lipid peroxidation and increased levels of glutathione [115]. NAC treatment significantly improved sleep and respiratory parameters indicated by reduced apnoea index, apnoea related-arousals, oxygen desaturations per hour and Epworth sleepiness score [115].…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, OSAS patients treated with NAC exhibited decreased lipid peroxidation and increased levels of glutathione [115]. NAC treatment significantly improved sleep and respiratory parameters indicated by reduced apnoea index, apnoea related-arousals, oxygen desaturations per hour and Epworth sleepiness score [115]. It is suggested that treatment with NAC over a prolonged period of time may reduce patient dependency on CPAP therapy [115].…”
Section: Discussionmentioning
confidence: 97%
“…Vitamin C and N-acetylcysteine (NAC) have shown interesting results in the reduction of OS in OSAS [ 7 ], and NAC reduces OS in OSAS through the reduction of peroxidized lipids and the increase in glutathione. Surprisingly, patients who received it continuously also had improvements in sleep parameters [ 86 ]. Vitamin C, on the other hand, proved to be effective in improving the endothelial function of OSAS patients in a study that took as its reference the diameter of the brachial artery, an indirect indicator of endothelial function [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…N-acetylcysteine reduces oxidative stress in OSAS patients by reducing peroxidized lipids and increasing glutathione. Furthermore, an improvement in PSG data has been found [86]. Vitamin C improves endothelial function in OSAS patients [100].…”
Section: The Role Of Antioxidant Therapymentioning
confidence: 92%
“…Macrophages also play a key role in this inflammatory process due to oxidative stress, producing numerous molecules and reactive oxygen species, like substances reactive to thiobarbituric acid, 8-OHdG, and asymmetric dimethylarginine [85]. Oxidative stress contributes to sleep behavior in patients with OSAS, and some authors suggest that the intake of antioxidants improves sleep quality [25,86]. However, most of the molecules are not tested in humans, and those tested in humans have not been studied in cohorts large enough to give indications of their use.…”
Section: Osas and Interleukinsmentioning
confidence: 99%